Neonatal mortality in Missouri home births, 1978-84. - Schramm, W F (1987)
A study was conducted of 4,054 Missouri home births occurring from 1978 through 1984. Of the 3,645 births whose planning status was identified, 3,067 (84 per cent) were planned to be at home. Neonatal mortality was elevated for both planned (17 observed deaths vs 8.59 expected deaths) and unplanned home births (45 observed vs 33.19 expected) compared with physician-attended hospital births. Nearly all of the mortality excess for planned home births occurred in association with lesser trained attendants (12 observed vs 4.42 expected), while for unplanned home births the excess was entirely among infants weighing 1500 grams or more (19 observed vs 3.50 expected). For planned home births attended by physicians, certified nurse-midwives, or Missouri Midwife Association recognized midwives, there was little difference between observed and expected deaths (5 observed vs 3.92 expected). There also was little difference in deaths for unplanned home births weighing less than 1500 grams (26 observed vs 29.69 expected) compared with hospital births. The study provides evidence of the importance of having skilled attendants present at planned home births.